Gender, humiliation, and global security : dignifying relationships from love, sex, and parenthood to world affairs - Lindner, Evelin (Contemporary psychology (Praeger Publishers), 2010)
"Gender, Humiliation, and Global Security: Dignifying Relationships from Love, Sex, and Parenthood to World Affairs aims at outlining the kind of change that needs to be made if we wish to create a less crisis-prone world. This audacious book describes a vision for an alternative future, showing how new approaches to love can dignify gender relations, sex, parenthood, and leadership, and how they can guide us to a world where all citizens can live dignified lives."--BOOK JACKET.